Transforming civil engineering: The role of nanotechnology and AI in advancing material durability and structural health monitoring - Ali Akbar Firoozi; Ali Asghar Firoozi; Mohammad Reza Maghami (Case Studies in Construction Materials, 2025)
This study explores the innovative integration of nanomaterials within civil engineering to boost material durability and advance infrastructure sustainability. Focusing on nano-silica and nano-titanium dioxide, the research enhances concrete properties, introducing functionalities like self-cleaning and pollution reduction. Nanosensors are employed for real-time structural health monitoring, increasing maintenance efficiency and safety. Empirical evidence from applications on the Golden Gate Bridge and in Singaporean high-rises demonstrates significant enhancements in material performance and environmental impacts. The research underscores the synergistic potential of combining nanotechnology with AI and IoT to create smarter, more resilient infrastructure systems. Results confirm substantial improvements in structural durability and functionality, highlighting the transformative impact of nanotechnologies in civil engineering.